Information technology in the new millennium what every modern manager should know - Dudeja, V D (New Delhi Commonwealth, 2000)
The advent of information technology supporting the computer provides new dimension of information availability and its use in business/industry.Use of internet in eveyday life hasbrought a revolution which emphasises an information support towards busine
Keywords: Information technology; Computer; Technology; Knowledge manage ment